2003
DOI: 10.4028/www.scientific.net/msf.433-436.423
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Electrical and Optical Mapping of Boron Related Complexes in 4H-SiC

Abstract: Boron related photoluminescence (PL) and capacitance transient spectroscopy (DLTS and MCTS) peaks have been investigated around SIMS craters. Enhancement of boron and hydrogen related PL was observed in the vicinity of the crater, whereas the concentration of electrically active boron as measured by MCTS has decreased considerably. Comparison of the boron MCTS peak behavior after electron and proton irradiation is presented. Possible defect models based on the obtained results are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2004
2004

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…In the present study an increase of the PL intensity of the PL lines was observed during the first hour of excitation. However for other samples [2][3][4], we did observe a very fast decrease of the PL line during the first few second of excitation. The PL intensity of the 3838Å line was after these few seconds constant, whereas the hydrogen related lines still were decreased in intensity.…”
Section: Pl Intensity (Cps)mentioning
confidence: 57%
See 3 more Smart Citations
“…In the present study an increase of the PL intensity of the PL lines was observed during the first hour of excitation. However for other samples [2][3][4], we did observe a very fast decrease of the PL line during the first few second of excitation. The PL intensity of the 3838Å line was after these few seconds constant, whereas the hydrogen related lines still were decreased in intensity.…”
Section: Pl Intensity (Cps)mentioning
confidence: 57%
“…The PL spectrum has also been observed after hydrogen plasma treatment [5]. The related PL spectrum for the 6H polytype was not reported in these previous works [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations